2019
DOI: 10.1590/2237-6089-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence and schizophrenia spectrum disorders: a critical review

Abstract: Introduction Emotional intelligence (EI) is a theoretical construct postulated by Mayer and Salovey to designate the ability to perceive, understand, use and manage emotions. The study of EI in schizophrenia offers new insights into the disorder’s cognitive and functional impacts. Objectives To comprehensively review studies analyzing EI impairment in schizophrenia spectrum disorders using standardized instruments. Methods Searches were run on MEDLINE/PubMed, Google Scholar, Cochrane, LILACS, Embase, Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
2
1
Order By: Relevance
“…Furthermore, although schizophrenia patients often exhibit deficits in working-memory abilities ( Walther et al, 2015 ), DSB performance of our patients was similar to controls, and thus was not associated with poor task performance. Finally, although patients exhibited inferior emotion perception abilities to controls ( Martins et al, 2019 ), it was not associated with gesture deficits in this study. This might be due to the nature of the stimuli we used, as neither the PKT nor the PLD task convey strong emotional states.…”
Section: Discussioncontrasting
confidence: 72%
“…Furthermore, although schizophrenia patients often exhibit deficits in working-memory abilities ( Walther et al, 2015 ), DSB performance of our patients was similar to controls, and thus was not associated with poor task performance. Finally, although patients exhibited inferior emotion perception abilities to controls ( Martins et al, 2019 ), it was not associated with gesture deficits in this study. This might be due to the nature of the stimuli we used, as neither the PKT nor the PLD task convey strong emotional states.…”
Section: Discussioncontrasting
confidence: 72%
“…They can also become spreaders who transmit the disease to others due to their neurocognitive impairment e.g. , lack of self-care, slowed perception, impaired problem-solving, reduced planning skills, and poor social cognition [ 19 , 31 - 33 ].…”
Section: Impacts Of Covid-19 On Psychiatric Patientsmentioning
confidence: 99%
“…González-Yubero et al (2019) found that EI predicted alcohol consumption among adolescents; while both AEI and TEI were found to predict alcohol consumption among adolescents, TEI was the most predictive. Finally, in their recent literature review, Martins et al (2019) concluded that, overall, addictions are associated with EI deficits compared to controls. EI has not been extensively considered in WT research.…”
Section: The Conceptual Differences Between Ability Emotional Intelli...mentioning
confidence: 99%